A microfluidic-multiwell platform for rapid phase mapping of surfactant solutions - Wang,H; Khodaparast,S; Carroll,J; Kelly,C; Robles,ESJ; Cabral,JT (Review of Scientific Instruments, 2020)
Measurement of the phase behavior and (meta)stability of liquid formulations, including surfactant solutions, is required for the understanding of mixture thermodynamics, as well as their practical utilization. We report a microfluidic platform with a stepped temperature profile, imposed by a dual Peltier module, connected to an automated multiwell plate injector and optical setup, for rapid solution phase mapping. The measurement protocol is defined by the temperature step ΔT ≡ T1 − T2 (100 °C), volumetric flow rate Q ≡ ΔV/Δt (50 μl/min), which implicitly set the thermal gradient ΔT/Δt (0.1–50 °C/min), and measurement time (which must exceed the intrinsic timescale of the relevant phase transformation). Furthermore, U-shaped microchannels can assess the reversibility of such transformations, yielding a facile measurement of the metastable zone width of the phase diagram. By contrast with traditional approaches, the platform precisely controls the cooling and heating rates by tuning the flow rate, and the absolute temperature excursion by the hot and cold thermal profile, which remain stationary during operation, thus allowing the sequential and reproducible screening of large sample arrays. As a model system, we examined the transition from the micellar (L1) to the liquid crystalline lamellar phase (Lα), upon cooling, of aqueous solutions of sodium linear alkylbenzene sulfonate, a biodegradable anionic surfactant extensively employed in industry. Our findings are validated with quiescent optical microscopy and small angle neutron scattering data.